Governing Cemeteries State Responses to the New Diversity in The Netherlands, Norway and France (Volume 30, Edition 1) - van den Breemer, Rosemarie (2021)
This book compares state responses to Muslim and humanist burial needs in three European countries. Such accommodation is typically understood in terms of national models. Van den Breemer, however, shows that policy responses in fact follow distinctive types of logic between the various levels of governance, and that material solutions matter as well. While indeed large legal and discursive national differences between states remain, in praxis they do the same. In a departure from this major finding, the book outlines a methodologically more coherent research agenda for the comparative study of religion, secularism, society, and state.